2022
DOI: 10.3390/cancers14071766
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Circulating Methylated Homeobox A9 DNA in Patients Undergoing Treatment for Recurrent Ovarian Cancer

Abstract: Methylated Homeobox A9 circulating tumor DNA (meth-HOXA9) has been suggested as a blood-based biomarker in epithelial ovarian cancer (EOC), although its prognostic significance remains unproven. The aim of the present study was to investigate the prognostic impact of meth-HOXA9 in patients with recurrent EOC. DNA was purified from 4 mL plasma and, following bilsulfite conversion, meth-HOXA9 was analyzed using a methylation-specific droplet digital PCR. Detection of meth-HOXA9 was reported as a percentage of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Survival outcomes were significantly inferior in patients with detectable HOXA9 methylation in ctDNA than in those without HOXA9 methylation (median progression-free survival [PFS]: 5.1 vs. 8.3 months, P < 0.0001; median OS: 9.5 vs. 19.4 months, P < 0.002) (100). Faaborg et al reported similar findings in a study of 126 patients (38.9% platinum sensitive and 81.7% with recurrent OC undergoing treatment with chemotherapy followed by maintenance therapy with PARP inhibitors or bevacizumab (101); with the increasing use of PARP inhibition in earlier lines of therapy, validation of these biomarkers in first line will be increasingly important.…”
Section: Cfdna and Ctdnamentioning
confidence: 58%
See 2 more Smart Citations
“…Survival outcomes were significantly inferior in patients with detectable HOXA9 methylation in ctDNA than in those without HOXA9 methylation (median progression-free survival [PFS]: 5.1 vs. 8.3 months, P < 0.0001; median OS: 9.5 vs. 19.4 months, P < 0.002) (100). Faaborg et al reported similar findings in a study of 126 patients (38.9% platinum sensitive and 81.7% with recurrent OC undergoing treatment with chemotherapy followed by maintenance therapy with PARP inhibitors or bevacizumab (101); with the increasing use of PARP inhibition in earlier lines of therapy, validation of these biomarkers in first line will be increasingly important.…”
Section: Cfdna and Ctdnamentioning
confidence: 58%
“…Faaborg et al. reported similar findings in a study of 126 patients (38.9% platinum sensitive and 81.7% with recurrent OC undergoing treatment with chemotherapy followed by maintenance therapy with PARP inhibitors or bevacizumab ( 101 ); with the increasing use of PARP inhibition in earlier lines of therapy, validation of these biomarkers in first line will be increasingly important.…”
Section: Treatment Response and Monitoring Progressionmentioning
confidence: 64%
See 1 more Smart Citation
“…This was recently illustrated in a study on patients with ovarian cancer. 41 Raunkilde et al ., 42 used the same methylation assay in a cohort of patients treated for mCRC with first-line therapy. An early evaluation of ctDNA response after the first cycle of chemotherapy revealed that PFS was 10.1 and 7.6 months, in ctDNA responders and nonresponders, respectively ( p = 0.02, HR = 0.43).…”
Section: Clinical Validity Of Ctdna: Response In Studies With Mcrcmentioning
confidence: 99%
“…5 On the other hand, a significant increase after the first treatment cycle seems to imply a poor prognosis. 6 The classification of the ctDNA kinetics should be based on objective criteria. The confidence interval (CI) of the measurement seems to be a reasonable measure in this respect and this approach is well-known from other analytics in clinical biochemistry.…”
mentioning
confidence: 99%